PERUBAHAN FENOTIP SAPI PERANAKAN ONGOLE, SIMPO, DAN LIMPO PADA KETURUNAN PERTAMA DAN KETURUNAN KEDUA (BACKCROSS) - Trifena (Trifena); I Gede Suparta Budisatria; Tety Hartatik (Faculty of Animal Science, Universitas Gadjah Mada, 2011)
The aims of the study was to analyze the phenotype of Ongole Grade, SIMPO, and LIMPO cows based on the exterior characteristics and body size of cattle, and to distinguish the phenotype of the first filial (F1) and the backcross(BC1) of SIMPO and LIMPO cows, reared by farmers at Pacitan, East Java. The study was conducted with purposive sampling method, involving 5 districts: Pacitan, Arjosari, Pringkuku, Nawangan, and Punung. Eighty four farmers asrespondents with total of 100 head cattle were used in the study. The results showed that the dominant coat color in Ongole Grade was white. However, none of crossbreed in F1 and BC1 had white color, but the color phenotype changeto brown and dark brown, which increase the dark intensity. The muzzle color of Ongole Grade was black, and changed to red in BC1. The hoof color’s of Ongole Grade was black, and brown for BC1. The color phenotype of F1 was similarto both color of Ongole Grade and BC1 phenotype. The increasing intensity of coat color in F1 to BC1 indicated that there was a combination of gene from Simmental or Limousin with F1 and BC1which containing of two or several set ofgenes. SIMPO and LIMPO cows had greater body size than those of Ongole Grade cows. The body’s sizes of BC1 was larger than F1 in SIMPO and LIMPO cows, which was influenced by increasing the effect of additive genes from F1 toBC1.(Keywords: Ongole Grade, SIMPO, LIMPO, First filial, Backcross, Phenotype of cattle)